2007
DOI: 10.1200/jop.0722001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Cognitive Impairment in Patients With Cancer

Abstract: Purpose: Cancer patients often report cognitive impairment, manifested as problems with concentration and memory, following cancer therapy. As part of a large multicenter survey of cancer patients undergoing treatment, we investigated the frequency and severity of self-reported problems with memory and concentration over time.Methods: A total of 595 patients undergoing treatment for solid tumors self-rated problems with memory and concentration, using an 11-point Likert scale (0 ϭ "not present" to 10 ϭ "as bad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 11 publications
(11 reference statements)
2
49
0
4
Order By: Relevance
“…Cognitive problems such as concentration and memory problems are frequently reported by cancer patients [1][2][3]. This has led to an increasing scientific focus on cognitive function (CF) after cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive problems such as concentration and memory problems are frequently reported by cancer patients [1][2][3]. This has led to an increasing scientific focus on cognitive function (CF) after cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations were performed after orchidectomy (surgical removing of the affected testicle) but prior to any additional treatment (baseline), and then at 1 year after end of treatment (follow-up). To our knowledge, this is the first prospective study of self-reported CF in TCPs, and the aims of the study were (1) to compare the proportions of TCPs with an increase of self-reported cognitive problems from baseline to 1-year follow-up among patients treated with different treatment modalities (no chemotherapy, one cycle of chemotherapy, or multiple cycles of chemotherapy) and (2) to study variables associated with an increase of self-reported cognitive problems from baseline to 1-year follow-up. Based on previous research, we hypothesized that (1) a larger proportion of TCPs treated with multiple cycles of chemotherapy have an increase of self-reported cognitive problems from baseline to 1-year follow-up compared with TCPs treated with no or with one cycle of chemotherapy; (2) an increase of self-reported cognitive problems from baseline to 1-year follow-up is significantly associated with psychological distress and fatigue at follow-up, but not with a decline in neuropsychological test performance.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have investigated the impact of chemotherapy, other studies have evaluated the impact of radiation therapy and hormonal therapies on cognitive function and found deficits in similar domains as with chemotherapy treatments (Castellon et al, 2004; Kohli et al, 2007; Schilder et al, 2009; Schilder et al, 2010; Schilder et al, 2012). Studies with comparison groups of patients treated with chemotherapy to those with hormonal therapies both show declines compared to healthy controls suggesting that hormone therapies can also lead to CRCI (Ahles, et al, 2010), and the combined treatment of tamoxifen and chemotherapy leads to greater difficulties than chemotherapy alone (Castellon, et al, 2004) (Palmer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies suggested that neurocognitive problems because of surgery, chemotherapy, or radiotherapy may negatively influence CNS cancer survivors' capacity of career problem-solving and decision-making (Green et al, 2005;Kohli et al, 2007;Gehring et al, 2008). Examples of cognitive dysfunctions that may lead to negative effects on career problem-solving and decisionmaking are delirium, attention, memory, or executive function (Green et al, 2005).…”
Section: Introductionmentioning
confidence: 99%